SISTEM PERINGATAN DINI BAHAYA KEBAKARAN MENGGUNAKAN MEKANISME JARINGAN (SENSOR NETWORK) BERBASIS MIKROKONTROLER ATMEGA 32 - , SUTRISNO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This design of monitoring tool prototype of fire alarm using network mechanism aims to facilitate human performance on home security surveillance, singly or integrated as a residential dwelling.This prototype is easy to use and also relieves its user. This prototype can be accessed from tens meter through the supervisory computer by wireless network (Wi-Fi). In this prototype, LED and buzzer are installed in one connection that named SS smoke sensor module 168p. Input values are obtained when the smoke swept sensor module that signed by the light of LED and sound from the buzzer.The information of those input values transmitted to the microcontroller, and then the microcontroller accesses the information and so transmits it through the wiznet moduleas the connector to the launcher that installed on the supervisor computer. The launcher works as the viewer of output values.